Exploring Artistic Creativity: A Psychological Review - Sumarsono, Sony; Handayaningrum, Warih; Sabri, Indar; Suyandoko, Welly (Journal of English Language and Education, 2025)
Creativity in the arts offers a profound exploration of the intricate interplay between creative expression and psychological dimensions, examining how emotions, thoughts, and personal experiences shape artistic output. This article analyzes the psychological stages of idea formation, obstacles encountered, and strategies to enhance creativity, highlighting the role of psychology in shaping unique works of art. It also explores artistic creativity as a tool for mental health, emphasizing its therapeutic potential and contribution to emotional well-being. Additionally, it examines the connection between creative expression and personal development, demonstrating how art fosters self-awareness and individual growth. By adopting a multidimensional perspective, the article provides a comprehensive understanding of artistic creativity as both a profound form of expression and a reflection of human psychology, offering insights into its broader psychological and developmental impacts.